The Effect of Foliar Fertilizer Application on the Growth and Production of Several Varieties of Mustard Plant (Brassica Juncea L) - Sitorus, Efbertias; Sihombing, Parsaoran; Panataria, Lince Romauli; Saragih, Meylin Kristina (ITScience (Information Technology and Science), 2024)
The study aims to determine the effect of foliar fertilizer on the growth and production of several varieties of mustard greens (Brassica juncea L). This study used a Factorial Randomized Block Design (RAK) consisting of two factors. The first factor is mustard greens varieties (V) consisting of 3 levels: V1 = Tosakan variety, V2 = Shinta variety, and V3 = Dora variety. The second factor is foliar fertilizer (P), consisting of 3 levels: P0 = control, P1 = 2 cc / l of water, and P2 = 4 cc / l of water. The parameters observed in this study were plant height and wet and dry Weight of plants. The results showed that the variety treatment significantly affected plant height, wet Weight and dry Weight of mustard greens. The highest growth and production were obtained in variety V1 (Tosakan), followed sequentially by variety V2 (Shinta) and variety V3 (Dora). Foliar fertilizer treatment significantly affected plant height, wet Weight and dry Weight of mustard greens. The higher the concentration of leaf fertilizer given up to 4 cc/l of water, the higher the growth and production of mustard plants. The interaction between variety treatment and leaf fertilizer concentration had no significant effect on all observed variables.